Effect of LASER photobiomodulation on the cell viabilities of periodontal ligament fibroblasts of older and younger individuals - An in vitro study - Aditi Singh; Soumya Bardvalli Gururaj; Shrinidhi Maji Shankar; Chethana Kunthur Chidambar; Kala Bhushan; Bharathi Poojary (Wolters Kluwer Medknow Publications, 2023)
Background and Objectives: Fibroblasts form the major cell type of the periodontal ligament and most often studied for periodontal regeneration. The aim of the present study was to investigate the effects of photobiomodulation (PBM) on aged periodontal fibroblasts and compare the viability of periodontal fibroblasts of older and younger individuals. Materials and Methods: A total of 32 patients were divided into four groups: A, B, C, and D. Groups A and C and B and D comprised of extracted teeth of older (>60 year) and younger individuals (<25 year), respectively. Extracted teeth from Groups A and B received PBM, (diode laser, 660 nm, 100 mW at 4J) whereas Groups C and D did not. Tissue from extracted teeth of all groups was processed and cultured and subjected to 3-(4,5 dimethylthiazol-2-yl)-2,5-diphenyl tetrazolium bromide assay to assess their viability. Results: The difference between the groups in terms of viability was significant (P < 0.0001). The mean viability of A and B (PBM) was 1.04 and 1.19, respectively. The mean viability for C and D (non-PBM) was 0.95 and 0.85, respectively. Conclusion: Older fibroblasts have lower viability than younger fibroblasts. PBM improves viability in both older and younger fibroblasts and more so in younger fibroblasts. However, more than one PBM would be required to sustain the effect longer.